The influence of patients' immigration background and residence permit status on treatment decisions in health care. Results of a factorial survey among general practitioners in Switzerland. (July 2016) - Drewniak, Daniel; Krones, Tanja; Sauer, Carsten; Wild, Verina
Abstract: This study examines the influence of patients' immigration background and residence permit status on physicians' willingness to treat patients in due time. A factorial survey was conducted among 352 general practitioners with a background in internal medicine in a German-speaking region in Switzerland. Participants expressed their self-rating (SR) as well as the expected colleague-rating (CR) to provide immediate treatment to 12 fictive vignette patients. The effects of the vignette variables were analysed using random-effects models. The results show that SR as well as CR was not only influenced by the medical condition or the physicians' time pressure, but also by social factors such as the ethnicity and migration history, the residence permit status, and the economic condition of the patients. Our findings can be useful for the development of adequate, practically relevant teaching and training materials with the ultimate aim to reduce unjustified discrimination or social rationing in health care. Highlights: A factorial survey is used to examine physicians' willingness to provide treatment. Focus of the study is equitable health care for minorities. Treatment is influenced by patients' origin and the residence permit status. Treatment is influenced by the patients' economic condition. Findings can be used for the development of teaching and training materials.